Sexualidade, adolescência e educação sexual a partir dos quereres e poderes da internet - Menin, Franciéle Trichez (2017)
Thinking about sexuality, adolescence and sexual education from the wills and powers of the internet led us to this research that, study aims to understand how the use of the Internet in the school space occurs, if there was sexual education in the schoolsanalysed, as well as how is the influence of the Internet on the sexuality of the adolescents surveyed. For this, we perform bibliographical and field research, with a qualitative and quantitative character. We categorize the following categories of research analysis: Internet and Adolescence, Adolescence and Sexuality, Adolescence and Sexual Education, Sexuality and Sexual Education. We used the collected material as historical contribution, based on the theoretical methodological reference of historical dialectical materialism. For the bibliographic research, we conducted the descriptive searches of our categories in the databases of theses and dissertations of the stricto sensu programs of the Paraná State Universities, totaling seven (07) institutions. We found seventeen (17) master's dissertations, however, they did not discuss the object of this research and we found research that related to all categories of analysis. Field research was carried out with the collection of data from fortytthree (43) adolescents and twenty-two (22) teachers, both from the high school in four (04) state colleges of the public network of the Francisco Beltrão – PR town. The colleges were listed from the largest number of students and teachers in the town, as well as their insertion in different social contexts, which allowed a broad view of the realities related to the research objective. Data collection was done by applying semi-open questionnaires to all participants through ten (10) questions each. Anchored in bibliographical and field research, we verify the way that Sexual Education and the use of the Internet is being carried out in educational institutions. According to the data obtained, it was possible to verify the lack of understanding of the Internet as a pedagogical tool, besides sporadic use and the importance of emancipatory Sexual Education during adolescence. Therefore, teachers are indispensable educators in the daily life of adolescents, they often don’t realize how important their job/action is for the development and training of adolescents. Similarly, they are unaware of the importance of Emancipatory Sexual Education in the classroom, since their formations don’t account for preparing them to exercise, safely, such a function. We emphasize in the course of the dissertation our struggle in defense of the continued formation of teachers, as well as the use of the internet as a pedagogical tool, to exercise an Emancipatory Sexual Education – In the classroom and beyond; In adolescents' lives. This training will contribute to the process of teaching and learning, enabling a healthy adolescence, in which individuals understand themselves and the other,personal and social respect.